Flexible genomic island conservation across freshwater and marine Methylophilaceae - Layoun, Paul; López-Pérez, Mario; Haro-Moreno, Jose M; Haber, Markus; Thrash, J Cameron; Henson, Michael W; Kavagutti, Vinicius Silva; Ghai, Rohit; Salcher, Michaela M (The ISME journal, 2024)
The evolutionary trajectory of Methylophilaceae includes habitat transitions from freshwater sediments to freshwater and marine pelagial that resulted in genome reduction (genome-streamlining) of the pelagic taxa. However, the extent of genetic similarities in the genomic structure and microdiversity of the two genome-streamlined pelagic lineages (freshwater "Ca. Methylopumilus" and the marine OM43 lineage) has so far never been compared. Here, we analyzed complete genomes of 91 "Ca. Methylopumilus" strains isolated from 14 lakes in Central Europe and 12 coastal marine OM43 strains. The two lineages showed a remarkable niche differentiation with clear species-specific differences in habitat preference and seasonal distribution. On the other hand, we observed a synteny preservation in their genomes by having similar locations and types of flexible genomic islands (fGIs). Three main fGIs were identified: a replacement fGI acting as phage defense, an additive fGI harboring metabolic and resistance-related functions, and a tycheposon containing nitrogen-, thiamine-, and heme-related functions. The fGIs differed in relative abundances in metagenomic datasets suggesting different levels of variability ranging from strain-specific to population-level adaptations. Moreover, variations in one gene seemed to be responsible for different growth at low substrate concentrations and a potential biogeographic separation within one species. Our study provides a first insight into genomic microdiversity of closely related taxa within the family Methylophilaceae and revealed remarkably similar dynamics involving mobile genetic elements and recombination between freshwater and marine family members.
Keywords: cultivation; genom bakteriální; jezera; genomic microdiversity; genomics; genomic islands; genome-streamlined bacteria; Genome, Bacterial; Phylogeny; Lakes; fylogeneze; Methylophilaceae; genomové ostrovy; Genomic Islands